A implementação de serviços socioassistenciais: uma análise da PAIF e seus desafios para a garantia das seguranças sociais - Costa, Eliete Cristina Rezende (2016)
Social Assistance policy on social security since the Brazilian Constitution of 1988 has been legitimized in the field of social protection especially from the implementation of the Social Assistance System, “SUAS” in 2004. The guarantee of social security is the repertoire of political functions and points to a series of acquisitions that materialize the conception of social protection. The decentralization, as “SUAS” guidelines, confers to municipalities the responsibility for the provision by social assistance services, among them, The Service of Protection and Integral Service to the Family – PAIF, that consist of main service of basic social protection system. This service aims to strengthen the protective function of families and prevent the occurrence of situations of social risk and vulnerability through strengthening family and community ties. The research analyzes the process of implementation of this service in Belo Horizonte, with the goal of mapping the elements that affect the implementation and that compromise the achievement of policy outcomes. The social assistance special features that fall into a typology of policies characterized by low programmability of the actions and the elevated interaction between technicians and users. This and other features put in relief the importance of street-level bureaucrat as a fundamental actor in the delivery of services and in the translation of the objectives of the policy, particularly in translation of social security from the implementation of the services. The literature on implementation of public policies and more specifically on the role of "streetlevel bureaucracy" served as a guide for the analysis. From a qualitative methodology and through the case study of two territories, the research focused on the perception of the technicians who work in Social Assistance reference Centers (CRAS), through nine semi structured interviews, seeking to understand how they perceive and face the challenges of implementation, or how to do the translation between the normative ideals of the politic and its operationalization in the actions offered under the PAIF. The results point to some challenges of the implementation process of the PAIF: conditions of "overlapping authority" over the daily lives of service and commitment to implementing the actions; the difficulties of intersectoral approach in the context of the action, which ultimately overwhelm services; the fragility of methodologies and intervention strategies that take account of the nature of the task, assistance in "loosely articulated systems"; the different interaction strategies developed by the technicians and users to define, in the end, the achievement or not of the scope of social security. The analysis points to the fact that the regulations are not enough to guide the delivery and that politics, rather than all, maybe, the role of street-level bureaucrat is fundamental as primary means of translating intentions into actions, if constituting in the main social assistance intervention technology of Social Assistance.